Improved Delivery of Cardiovascular Care (IDOCC): Findings from Narrative Reports by Practice Facilitators - Liddy, Clare (Prev Med Rep, 2016)
Practice facilitation can help family physicians adopt evidence-based guidelines. However, many practices struggle to effectively implement practice changes that result in meaningful improvement. Building on our previous research, we examined the barriers to and enablers of implementation perceived by practice facilitators (PF) in helping practices to adopt the Improved Delivery of Cardiovascular Care (IDOCC) program, which took place at 84 primary care practices in Ottawa, Canada between April 2008 and March 2012. We conducted a qualitative analysis of PFs’ narrative reports using a multiple case study design. We used a combined purposeful sampling approach to identify cases that 1) reflected experiences typical of the broader sample and 2) presented sufficient breadth of experience from each project step and family practice model. Sampling continued until data saturation was reached. Team members conducted a qualitative analysis of reports using an open and axial coding style and a constant comparative approach. Barriers and enablers were divided into five constructs: structural, organizational, provider, patient, and innovation. Narratives from 13 practice sites were reviewed. A total of 8 barriers and 11 enablers were consistently identified across practices. Barriers were most commonly reported at the organizational (n = 3) and structural level, (n = 2) while enablers were most common at the innovation level (n = 6). While physicians responded positively to PFs’ presence and largely supported their recommendations for practice change, organizational and structural aspects such as lack of time, minimal staff engagement, and provider reimbursement remained too great for practices to successfully implement practice-level changes. Trial Registration: ClinicalTrials.gov, NCT00574808